Scholars’ Attention to the Companions: A Bibliographic Study of Works Written about the Sahabah: عناية العلماء بالصحابة: دراسة ببليوغرافية في المؤلفات التي أُلفت حول الصحابة - Hüseyin Elmhemıt (Demak Universal Journal of Islam and Sharia, 2025)
Objective: This study aims to present a comprehensive bibliographic examination of scholarly works written about the Companions (al-Sahabah) of Prophet Muhammad (peace be upon him). Its main objective is to document, classify, and analyze the intellectual efforts of Muslim scholars who, across generations, preserved the legacy and virtues of these noble individuals. Theoretical framework: Grounded in the theoretical framework of Islamic historiography and ‘ilm al-rijāl (biographical evaluation), the research highlights how scholars defined, categorized, and transmitted knowledge about the Companions, emphasizing their pivotal role in sustaining the authenticity of Islamic teachings. Literature review: The literature review reveals that studies on the Companions have long occupied a central position in Islamic scholarship. From early biographical dictionaries and Ma‘ājim al-Sahabah to specialized works focusing on virtues, hadith transmitters, and personal accounts, the diversity of these writings demonstrates the richness of Muslim intellectual tradition. Classical scholars such as Ibn Sa‘d, Ibn Hajar, and al-Dhahabi contributed profoundly to shaping the methodology for documenting the Companions’ lives. Methods: Methodologically, this research adopts an inductive and descriptive approach. It surveys a wide range of sources—both printed works and manuscripts—extending chronologically up to the death of the eminent scholar Ibn ‘Abidin (1252/1836). Each source is recorded with bibliographic precision, including information about authorship, location, and reference numbers. The study excludes general historical works, focusing instead on texts devoted specifically to the Companions. Results: The findings reveal four major categories of scholarly works: general compilations on the Companions, Ma‘ājim al-Sahabah, treatises on their virtues, and thematic studies on particular aspects such as Qur’anic manuscripts, poetry, and classifications. Collectively, these writings reflect the sustained reverence and scholarly rigor devoted to the Companions throughout Islamic history. Implications: The study’s implications extend to the preservation of Islamic heritage, highlighting the depth and continuity of Muslim scholarly engagement with early Islamic figures. Novelty: Its novelty lies in its systematic bibliographic organization of dispersed sources, providing an essential reference for future researchers in Islamic history, hadith studies, and manuscript preservation.